Transformation of Forest Soils in Iowa (United States) under the Impact of Long Term Agricultural Development - Chendev, Yu.G; Burras, C.L; Sauer, T.J (Eurasian soil science, 2012)
The evolution of automorphic cultivated soils of the Fayette series (the order of Alfisols)—close analogues of gray forest soils in the European part of Russia—was studied by the method of agrosoil chronosequences in the lower reaches of the Iowa River. It was found that the old-arable soils are characterized by an increase in the thickness of humus horizons and better aggregation; they are subjected to active biogenic turbation by rodents; some alkalization of the soil reaction and an increase in the sum of exchangeable bases also take place. These features are developed against the background of active eluvial–illuvial differentiation and gleyzation of the soil profiles under conditions of a relatively wet climate typical of the ecotone between the zones of prairies and broadleaved forests in the northeast Central Plains of the United States.